Sart-Kalmyks of Kyrgyzstan: a Brief Ethnographic Essay - B. Kh. Borlykova; B. V. Menyaev (Научный диалог)
In this article, based on published, archival and personal field materials of the authors (2009—2021), a brief ethnographic sketch of the Sart-Kalmyks of Kyrgyzstan is given. Sart-Kalmyks (Issyk-Kul, or Karakol Kalmyks / Kalmaks) are a relatively small Mongol-speaking people of Oirat origin who practice Islam. The article briefly examines the ethnonym “Sart-Kalmyk”, the history of the study of the Sart-Kalmyks, ethnic his-tory, ethnic composition, population, language, writing, economy, material and spiritual culture of the Sart-Kalmyks in the late XIX — early XXI centuries. Despite the paucity of sources, the authors tried to restore the ethnic origin and ethnic composition of the Sart-Kalmyks, which consists of more than twenty clans. During the expedition of 2021, the authors of the article found a copy of the manuscript of the “Kyrgyz-Sart-Kalmyk-Russian Dictionary”, compiled by S. S. Nasynbatov in the 1990s. It is shown that in the Sart-Kalmyk language words related to Buddhist vocabulary were found, which is evidence that they once included Buddhists. Particular attention is paid to the changes taking place in the modern life of the Sart-Kalmyks of Kyrgyzstan. It is concluded that the long-term residence of the Sart-Kalmyks in a different ethnic environment actively influenced the loss of their native language, writing, traditions and led to ethnic and ethno-cultural changes.